Differential requirements of aPKC activity within different epithelial tissues - Prudêncio, Pedro António Pereira (2014)
Epithelial tissues are essential during morphogenesis and organogenesis. During development, epithelial tissues undergo several different remodeling processes, from cell intercalation to cell change shape. An epithelial cell has a highly polarized structure, which is important to maintain tissue integrity. The mechanisms that regulate and maintain apicobasal polarity and epithelial integrity are mostly conserved among all species and in different tissues within the same organism. aPKC-PAR complex localizes in the apical domain of polarized cells, and its function is essential for apicobasal polarization and epithelial integrity. In this work we characterized two novel alleles of aPKC: a temperature sensitive allele (aPKCTS), which has a point mutation on a kinase domain, and another allele with a point mutation on a highly conserved amino acid within the PB1 domain of aPKC (aPKCPB1). Analysis of the aPKCTS mutant phenotypes, lead us to propose that during development different epithelial tissues have differential requirements of aPKC activity. More specifically, our work suggests de novo formation of adherens junctions (AJs) is particularly sensitive to sub-optimal levels of apkc activity. Analysis of the aPKCPB1 allele, suggests that aPKC is likely to have an apical structural function mostly independent of its kinase activity. Altogether our work suggests that although loss of aPKC function is associated to similar epithelial phenotypes (e.g., loss of apicobasal polarization and epithelial integrity), the requirements of aPKC activity within these tissues are nevertheless likely to vary.